The Pathophysiology and Management of Coprophagia: A Report of Two Cases and Literature Review. (15th November 2018) - Azizi, Heela; Khan, Tasmia; Canale, Cecilia; Kallikkadan, Jisha; Leung, Ivan; Kahn, Alexa; Rimawi, Dina; Williams, Shantale; Obegolu, Chidubem Matthew; Paul, Sharon; Chaudhry, Shazia; Ojimba, Chiedozie; et al.
Abstract : Coprophagia is a rare and distressing disorder characterized by symptoms of compulsive consumption of feces. Several attempts have been made in literature to explore the pathophysiology, management, and outcomes of this disorder. However, critical questions remain, related to characterizing effective management, features of associated comorbidities, time to recovery of symptoms, sustainability of recovery, and the determinants of outcomes. Unfortunately, there is a dearth of available literature addressing these questions. We present two cases of patients with coprophagia in seeking to address these questions. Common symptoms of thought content disorder related to coprophagic behavior are noted in both cases. A shorter time to resolution of coprophagia is noted in one of the patients compared to previously reported studies. Recent and pertinent literature was reviewed and the implications for diagnosis and management of coprophagia are discussed.